Nitric Oxide Alleviates Salt Stress Inhibited Photosynthetic Performance by Interacting with Sulfur Assimilation in Mustard - Fatma, Mehar; Masood, Asim; Per, Tasir S.; Khan, Nafees A. (Frontiers in Plant Science, 2016)
The role of nitric oxide (NO) and/or sulfur (S) on stomatal and photosynthetic responses was studied in mustard (Brassica juncea L.) in presence or absence of salt stress. The combined application of 100 µM NO (as sodium nitroprusside) and 200 mg S kg-1 soil (excess-S) more prominently influenced stomatal behaviour, photosynthetic and growth responses in the absence of salt stress and alleviated salt stress effects on photosynthesis. Plants receiving combined treatment of NO plus excess-S showed well-developed thylakoid membrane and properly stacked grana lamellae under salt stress, while the chloroplasts from salt-stressed plants had disorganized thylakoids. Moreover, the leaves from the NO and excess-S treated plants exhibited lower superoxide ion accumulation under salt stress, induced activity of ATP-sulfurylase (ATPS), catalase (CAT), ascorbate peroxidase (APX) and glutathione reductase (GR) and optimized NO generation that helped in minimizing oxidative stress. The enhanced S-assimilation of these plants resulted in increased production of cysteine (Cys) and glutathione (GSH) reduced. These findings indicated that NO influenced photosynthesis under salt stress by regulating oxidative stress and its effects on S-assimilation, an antioxidant system and NO generation.The results suggest that NO improves photosynthetic responses of plants grown under salt stress more effectively when plants received excess-S. Thus, excess-S conditions may be adopted for higher impact of NO in the reversal of salt stress effects on photosynthesis.